Characterization of the Anodic Film and Corrosion Resistance of an A535 Aluminum Alloy after Intermetallics Removal by Different Etching Time - Suwaree Chankitmunkong; Dmitry Eskin; Chaowalit Limmaneevichitr; Nattarat Kengkla; Onnjira Diewwanit (My University, 2022)
The objective of this study was to improve the corrosion resistance of an A535 alloy by removing intermetallics on the alloy surface by alkaline etching to improve the morphologies and properties of the anodic film that was sealed with different sealants. It was found that alkaline etching for 4 min was suitable for dissolving intermetallic particles and simultaneously providing sufficient roughness for the adhesion of an oxide film to the Al matrix. The effect of alkaline etching revealed that a decrease in the intermetallic fraction from 21% to 16% after etching for 2 and 4 min, respectively, corresponded to the increase in the surface roughness, thickness, and consistency of the anodic film. It was also demonstrated that the surface morphology of the anodic films after stearic acid sealing was more uniform and compact than that after nickel fluoride sealing. The electrochemical polarization curves and salt spray test proved that the alloy etched for 4 min and sealed with stearic acid had better corrosion resistance as compared with the aluminum alloy sealed with nickel fluoride.
Keywords: Anodic Oxide Films and Nanostructures